In vitro anther culture as efficiently applied technique for doubled haploid production of wheat (Triticum aestivum L.) - Kanbar Osama Zuhair (Ratarstvo i Povrtarstvo, 2021)
In vitro anther culture is the most commonly-used technology for doubled haploid production in wheat (Triticum aestivum L.) and various cereals. The technology application allows the genetic attainment of homozygous pure lines from heterozygous breeding material in a single generation, and has become a rapid alternative to the conventional breeding methods. This technology also contributes to more accurately assess QTL × environmental interactions and has been applied in: genetic researches for marker-trait association study, genomics and as a target for transformation, genetic engineering, gene mapping, and mapping of quantitative trait loci (QTLs). This paper reviews the most important factors that limit the efficiency of winter wheat (Triticum aestivum L.) anther culture, such as genotype dependency and albinism, in addition to other affecting factors including the collection time of tillers and physiological growth environments of plants. Factors that improve the efficiency of wheat anther culture in mitigating both genotypic dependency and albinism have been included in this review, too, for example, genetic improvements by following a strategy to realize this purpose through using responsive breeding material for crossing, application of convenient stress pre-treatments (cold pre-treatments, heat shock treatment, colchicine, hormones, and chemicals) to induce androgenesis, and improvement of the composition of anther culture media and culture conditions. We have also highlighted the methods of chromosome doubling for the haploid wheat produced by anther culture androgenesis, such as spontaneous chromosome doubling or use of colchicine and anti-mitotic chemicals at an early stage of anther culture or as root immersion treatment.